2004
DOI: 10.1159/000078639
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ε-(γ-Glutamyl)lysine in Human Diabetic Nephropathy Results from Increased Expression and Cellular Release of Tissue Transglutaminase

Abstract: Introduction: Diabetic nephropathy (DN) is the leading cause of chronic kidney failure, however the mechanisms underlying the characteristic expansion of the extracellular matrix (ECM) in diabetic kidneys remain controversial and unclear. In non-diabetic kidney scarring the protein crosslinking enzyme tissue transglutaminase (tTg) has been implicated in this process by the formation of increased Ε-(γ-glutamyl)lysine bonds between ECM components in both experimental and human disease. Studies in db+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 78 publications
2
27
0
Order By: Relevance
“…We observed increased expression of two probes of transglutaminase 2 (1433428_x_at, 1437277_x_at) in the db/db mice. It has been reported that tissue transglutaminase enzyme is implicated in protein crosslinking by the formation of increased ε-(Á-glutamyl) lysine bonds between extracellular matrix components in the diabetic kidneys of both db/db mice and human patients with diabetes (19). The present study revealed that this increased expression was markedly reversed by treatment with astaxanthin.…”
Section: ------------------------------------------------------------supporting
confidence: 53%
“…We observed increased expression of two probes of transglutaminase 2 (1433428_x_at, 1437277_x_at) in the db/db mice. It has been reported that tissue transglutaminase enzyme is implicated in protein crosslinking by the formation of increased ε-(Á-glutamyl) lysine bonds between extracellular matrix components in the diabetic kidneys of both db/db mice and human patients with diabetes (19). The present study revealed that this increased expression was markedly reversed by treatment with astaxanthin.…”
Section: ------------------------------------------------------------supporting
confidence: 53%
“…The transglutaminase-specific bonds, N-ε-γ-glutamyl lysine chain cross-links, were stained with the mouse monoclonal 81D4 antibody (ab424 Abcam) [28, 29] on frozen artery sections. The staining was quantified with visual semiquantification.…”
Section: Methodsmentioning
confidence: 99%
“…Morphologically, it is characterized by excessive renal ECM accumulation in the glomeruli and tubulointerstitial space, causing glomerulosclerosis and tubulointerstitial fibrosis. A role for TGase 2 in the pathogenesis of DN has been reported in both the streptozotocin (STZ)-induced model of type 1 diabetes [90] and human diabetic kidney disease [91]. Additionally, increased TGase 2-mediated ε-(␥ -glutamyl)lysine cross-link formation is tightly associated with both glomerular and tubulointerstitial ECM expansion in diabetic kidneys.…”
Section: F Renal Injurymentioning
confidence: 99%